2013
DOI: 10.3233/wor-121553
|View full text |Cite
|
Sign up to set email alerts
|

Health survey of U.S. long-haul truck drivers: Work environment, physical health, and healthcare access

Abstract: OBJECTIVE: While trucking in industrialized nations is linked with driver health afflictions, the role of trucking in U.S. truckers' health remains largely unknown. This paper sheds light on links between the trucking work environment and drivers' physical health. METHODS: Using a cross-sectional design, 316 truckers were enrolled in the Healthy Trucker Survey. Questions included work history, physical and mental health, and healthcare access. PASW 18 was used to examine patterns among factors. PARTICIPANTS: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
165
2
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 17 publications
8
165
2
7
Order By: Relevance
“…Obesity rates have become endemic to almost all parts of the world, but data from previous studies [Moreno et al, ; Martin et al, ; Saberi et al, ; Apostolopoulos et al, ; Sangaleti et al, ; Sieber et al, ; Rosso et al, ] and the current investigation suggest that long‐haul truck drivers are significantly more obese than the general population. Abdominal obesity was highly prevalent in our group of drivers.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Obesity rates have become endemic to almost all parts of the world, but data from previous studies [Moreno et al, ; Martin et al, ; Saberi et al, ; Apostolopoulos et al, ; Sangaleti et al, ; Sieber et al, ; Rosso et al, ] and the current investigation suggest that long‐haul truck drivers are significantly more obese than the general population. Abdominal obesity was highly prevalent in our group of drivers.…”
Section: Discussioncontrasting
confidence: 57%
“…This sets up a hormonal milieu that may alter appetite‐related input to the hypothalamus, resulting in altered energy balance [Marqueze et al, ], and; ultimately, body weight and other cardiovascular risk factors will be affected. Making matters worse, many long‐haul drivers lack basic health insurance coverage, and work hours make it difficult to seek medical care [Apostolopoulos et al, ]. Despite these dramatic health disparities, efforts to mitigate the multiple deleterious impacts on driver health endemic to the long‐haul trucking profession, particularly those associated with working conditions of drivers, have been sporadic and piecemeal [Lemke and Apostolopoulos, ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 6.5-23.8% of drivers report eating 5 or more daily servings of fruits and vegetables 16, 19 with daily serving estimates ranging from 1.7 to 2.8 19, 20 . In two studies 70-90% of drivers reported not regularly engaging in exercise 15, 21 . In one study 27.1% of drivers reported zero days per week with 30 minutes of moderate exercise; 3 in another, the median weekly minutes of physical activity was zero 18 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the common services consists of health risk appraisals (HRAs) for the purpose of detecting early signs of illness and adverse lifestyle factors. Other purposes of HRAs are pre-employment surveillance [3], screening for the occurrence of stress in a company [4] or assessing the general health status in a special occupation [5]. HRAs are commonly performed as part of general health care as well, but OHS can also include working conditions in the assessment, thus adding an important dimension to health promotion in an occupational setting.…”
Section: Introductionmentioning
confidence: 99%